A pathway towards true sustainability: a recognition foundation of sustainable supply chain management - Gold, Stefan; Schleper, Martin C. (Elsevier, 2017)
Sustainable supply chain management has developed at an exponential rate into a distinct research field, but its progress towards sustainability is rather modest, and a coherent theoretical foundation for guiding companies towards a stronger integration of sustainability into their operations and supply chains is still missing. This article outlines how the tradition of critical management studies could foster higher levels of sustainable business and sustainable supply chains. We argue that the underlying instrumental logic of contemporary corporate engagement with sustainability, driven by stakeholder pressures, is a key obstacle when aiming for ‘truly’ sustainable supply chains. Referring to a recognition perspective may dissolve the reified pursuit of profit-seeking and other merely economic performance targets to recall the genuine—and in its essence truly radical—claim that the concept of sustainable development is inherently a normative one imposed on all of us. Recognition may lead the way for companies to adopt a caring stance for people and the surrounding environment and to respond to the legitimate expectations of all groups in society while conceiving themselves as an integral part of such a society. We conclude by discussing how far the theoretical perspective of recognition is enrooted in the European tradition of institutionalised business–society relationships and therefore could be seen as a rediscovery of a genuinely European way of making business and managing supply chains.